Banking finance experts consensus on compliance in US bank holding companies: An e-Delphi study - Sophia Beckett Velez; Michael Neubert; Daphne Halkias (Journal of Risk and Financial Management, 2020)
Compliance measures emphasized in the Dodd-Frank Bill 2010, Section 165 is a response to the 2008 financial crisis, that requires large banks to maintain a minimum capital ratio. The Federal Reserve Bank (Fed) regulates capital of Bank Holding Companies (BHC) through compliance Supervisory Capital Assessment Program (SCAP) 2009 and Comprehensive Capital Adequacy Review (CCAR) 2011 annual stress test of capital. The Fed imposed a minimum capital ratio of 8% that has derailed the risk management objective of capital adequacy, as bank managers are forced to take on more risk to meet the capital ratio. This study concerns senior manager practices that can be effective in meeting compliance requirements posed by the Fed for BHCs. Through a qualitative e-Delphi study, 10 banking finance experts were convened to build consensus on senior manager's practices that can be effective in meeting compliance requirements. Data were collected from three electronic questionnaires submitted through Qualtrics. Data were analyzed using theoretical triangulation, coding, and thematic analysis. Four important considerations were identified that could bolster compliance measures effectiveness: (a) emphasis placed on understanding regulatory consultant compliance, (b) maintenance of effective and independent compliance align to organizational objectives, (c) clear definition of data source for compliance analytics. These considerations of compliance practices may help senior bank managers reduce risky behaviors and investments that cause significant bank losses.
Keywords: 330; BHC; capital regulation; compliance; compliance analytics; risk management